2017
DOI: 10.2503/hortj.mi-126
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Flowering-related Genes and Flowering Response in Relation to Blue Light in <i>Gypsophila paniculata</i>

Abstract: The flowering response to monochromatic light and flowering-related genes underlying this response need to be characterized to efficiently use light-emitting diodes for lighting culture. The flowering response to far-red light has been well studied in long-day cut flowers, but there have been few studies investigating the response to blue light. Flowering and the expression of the G. paniculata homologs of the FLOWERING LOCUS T and SUPPRESSOR OF OVEREXPRESSION OF CONSTANS 1 genes (GpFT, GpSOC1) were not previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…FKF1 has three domains: LOV, F-box, and KELCH repeat. In A. thaliana , it forms a gene family with ZTL [ 20 ]. ZTL has been reported to have a different function from FKF1 and is involved in the decomposition of TIMING OF CAB EXPRESSION 1 (TOC1), one of the components of the circadian clock [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FKF1 has three domains: LOV, F-box, and KELCH repeat. In A. thaliana , it forms a gene family with ZTL [ 20 ]. ZTL has been reported to have a different function from FKF1 and is involved in the decomposition of TIMING OF CAB EXPRESSION 1 (TOC1), one of the components of the circadian clock [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this way, FKF1 plays an essential role in flowering promotion by blue light. As FKF1 in long-day plants, it is suggested that the Gypsophila FKF1 homolog is involved in flowering promotion, besides A. thaliana [ 20 , 21 ]. Reportedly, OsFKF1 promotes flowering in rice, a short-day plant, regardless of the photoperiod condition [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of LED radiation treatment under dark conditions on the expression of FT and SOC1 or their homologs has been previously reported in Arabidopsis and G. paniculata Hori et al, 2011;Shibuya et al, 2017 . According to these studies, SOC1 expression was induced by far-red light, FT and SOC1 expressions were induced by blue light, and flowering was Days to flower budding after the start of LED radiation were shown.…”
Section: Expression Analysis Of Flowering-related Genesmentioning
confidence: 80%
“…In an earlier assessment, expression of the SOC1 homolog was found to be induced by far-red, and expression of neither the SOC1 homolog nor the FT homolog was induced by blue light in G. paniculata 'Bristol Fairy', in which flowering was promoted by far-red light but not blue light Hori et al, 2011 . A possible mechanism for this flowering response to blue light may be associated with variation in nucleotide sequences of the promoter region of the FT homolog, rather than with the function of the homologs of FKF1 and GI, which are involved in blue light signaling Shibuya et al, 2017 . Conversely, in the present study, changes in the levels of both EgFTL and EgSOC1L corresponded to the flowering response in FR and B, suggesting that a variable response of a common gene upstream of EgFTL and EgSOC1L to far-red and blue lights result in differences in flowering response to these wavelengths. In situ analysis of mRNA localization of these genes will be necessary to confirm their function.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the over-accumulation of APETALA2 / PETALOSA ( AP2 / PET ) due to the defects of miR172 binding reduces the AG expression in the stamens, leading to the double flower phenotype likewise [ 9 , 10 ]. Although this model has been verified in many ornaments, it remains unclear whether it is true in G. paniculata [ 15 ].…”
Section: Introductionmentioning
confidence: 99%